(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Background Social problem-solving skills have been identified as being crucial to social competency which is related to successful life adjustment. Researcher supported the idea that knowledge and use of social problem-solving skills are important aspects of mental health and behavioural adjustment. Therefore the need to explore social problem-solving skills arises as it has psychological and behavioural concern for the children well-being.Aim The objective of the present study is to explore social problem-solving skills in children while they face real-life problem situations. In addition, it explored the problem-solving styles followed by the children.Method The study employed an exploratory research design to explore social problem-solving skills in children. Data was collected with the help of interview method. The region selected for the study belongs to government schools of Mohali, Punjab. Seventh-grade children remained the subject under study.Results Results revealed that children are impulsive and reactive to the problem situations which indicated poor problem-solving skills in children. Children believed to follow impulsive and avoidance approach to the real-life problems rather than employing a rational approach and finding the best solutions to the problem.Conclusion The qualitative data analysis revealed children are very impulsive and aggressive in their approach while facing any problematic situation in school and at home.